Prevalence of Sensitization to Food and Inhalant Allergens in Patients with Atopic Dermatitis in Gorgan, North of Iran - Mohammad Sobhani Shahmirzadi; Jabbar Parhiz; Bagher Pahlevanzadeh; Masoud Mohammadi; Mohsen Ebrahimi (Journal of Clinical and Basic Research, 2019)
Background and objectives: Atopic dermatitis is a chronic inflammatory allergic disease that specifically affects the skin. The incidence of this disease is influenced by genetic and physical stimuli, hormones, stress and food and inhalants allergens. Given the increasing prevalence of atopic dermatitis, it is important to identify food and inhalant allergens associated with the disease. The purpose of this study was to evaluate prevalence of sensitization to food and inhalant allergens in children with atopic dermatitis. Methods: This cross-sectional study was performed on 56 children (29 boys and 27 girls) with atopic dermatitis who were referred to the Dezyani Asthma and Allergy Clinic in Gorgan between 2016 and 2017. Atopic dermatitis was confirmed via the Prick test. Data were analyzed using SPSS 16 at a significant level of 0.05. Results: Average age of the subjects was 4.26 ± 3.79 years. The most common inhalant allergens were mite (35.7%) and salt grass (3.6%) and the most common food allergens were egg white (35.7%) and cow's milk (26.8%). Conclusion: Considering the high prevalence of food allergy in the studied population, it is necessary to reduce the severity of allergic reactions and its consequent treatment costs by observing the principles of a healthy diet and lifestyle.